Use of Live Interactive Webcasting for an International Postgraduate Module in eHealth: Case Study Evaluation - Jones, Ray B; Maramba, Inocencio; Boulos, Maged N Kamel; Alexander, Tara (JMIR Publications, 2009)
Background Producing "traditional" e-learning can be time consuming, and in a topic such as eHealth, it may have a short shelf-life. Students sometimes report feeling isolated and lacking in motivation. Synchronous methods can play an important part in any blended approach to learning. Objective The aim was to develop, deliver, and evaluate an international postgraduate module in eHealth using live interactive webcasting. Methods We developed a hybrid solution for live interactive webcasting using a scan converter, mixer, and digitizer, and video server to embed a presenter-controlled talking head or copy of the presenter's computer screen (normally a PowerPoint slide) in a student chat room. We recruited 16 students from six countries and ran weekly 2.5-hour live sessions for 10 weeks. The content included the use of computers by patients, patient access to records, different forms of e-learning for patients and professionals, research methods in eHealth, geographic information systems, and telehealth. All sessions were recorded-presentations as video files and the student interaction as text files. Students were sent an email questionnaire of mostly open questions seeking their views of this form of learning. Responses were collated and anonymized by a colleague who was not part of the teaching team. Results Sessions were generally very interactive, with most students participating actively in breakout or full-class discussions. In a typical 2.5-hour session, students posted about 50 messages each. Two students did not complete all sessions; one withdrew from the pressure of work after session 6, and one from illness after session 7. Fourteen of the 16 responded to the feedback questionnaire. Most students (12/14) found the module useful or very useful, and all would recommend the module to others. All liked the method of delivery, in particular the interactivity, the variety of students, and the "closeness" of the group. Most (11/14) felt "connected" with the other students on the course. Many students (11/14) had previous experience with asynchronous e-learning, two as teachers; 12/14 students suggested advantages of synchronous methods, mostly associated with the interaction and feedback from teachers and peers. Conclusions This model of synchronous e-learning based on interactive live webcasting was a successful method of delivering an international postgraduate module. Students found it engaging over a 10-week course. Although this is a small study, given that synchronous methods such as interactive webcasting are a much easier transition for lecturers used to face-to-face teaching than are asynchronous methods, they should be considered as part of the blend of e-learning methods. Further research and development is needed on interfaces and methods that are robust and accessible, on the most appropriate blend of synchronous and asynchronous work for different student groups, and on learning outcomes and effectiveness.